2023
DOI: 10.3389/fphys.2023.1083643
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D-VDR (vitamin D receptor) alleviates glucose metabolism reprogramming in lipopolysaccharide-induced acute kidney injury

Abstract: Background: Our previous study showed that vitamin D (VD)-vitamin D receptor (VDR) plays a nephroprotective role in lipopolysaccharide (LPS)-induced acute kidney injury (AKI). Recently, glucose metabolism reprogramming was reported to be involved in the pathogenesis of AKI.Objective: To investigate the role of VD-VDR in glucose metabolism reprogramming in LPS-induced AKI.Methods: We established a model of LPS-induced AKI in VDR knockout (VDR-KO) mice, renal proximal tubular-specific VDR-overexpressing (VDR-OE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…NO plays an important role in angiogenesis and can promote the survival, proliferation, and migration of endothelial cells. It was reported that VD/VDR attenuated artery remodeling and endothelial dysfunction via the AMPK/eNOS in ischemia or LPS induced tissue injury 20–22 . However, the underlying mechanism is not clear.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…NO plays an important role in angiogenesis and can promote the survival, proliferation, and migration of endothelial cells. It was reported that VD/VDR attenuated artery remodeling and endothelial dysfunction via the AMPK/eNOS in ischemia or LPS induced tissue injury 20–22 . However, the underlying mechanism is not clear.…”
Section: Introductionmentioning
confidence: 98%
“…It was reported that VD/VDR attenuated artery remodeling and endothelial dysfunction via the AMPK/ eNOS in ischemia or LPS induced tissue injury. [20][21][22] However, the underlying mechanism is not clear. Adrenomedullin (ADM) is a 52-amino acid peptide originally isolated from extracts of human pheochromocytoma belonging to the calcitonin gene-peptide superfamily, which also includes calcitonin, calcitonin gene-related peptides, and islet amyloid protein.…”
mentioning
confidence: 99%